The PENGARUH GRUP WHATSAPP TERHADAP PARTISIPASI MAHASISWA DALAM EVALUASI AKADEMIK: STUDI KASUS DI FISIP UNIVERSITAS PALANGKA RAYA (UPR) - Salsabila, Chelsea Novitria; Putri, Oktavia Ramadhani; Rhama, Bhayu; Selvia, Fitriana; Suprayitno, Suprayitno (Jurnal Administrasi Pendidikan Indonesia, 2025)
This study aims to explore the effect of WhatsApp group usage on the participation of students at the Faculty of Social and Political Sciences (FISIP) of Palangka Raya University (UPR) in filling out semester academic evaluation questionnaires. In the digital age, social media such as WhatsApp plays an important role in supporting academic communication and collaboration between lecturers and students. This study uses a quantitative descriptive approach with simple linear regression analysis. The population consists of 150 people with a sample size of 108 and a 95% confidence level determined using the Krejcie and Morgan formula with purposive sampling technique. The results show that WhatsApp groups have a positive and significant influence on student participation, contributing 33.2% to the increase in student participation, while 66.8% is influenced by other factors outside the scope of this study. These findings are in line with previous studies that state that WhatsApp can increase engagement and motivation to learn. This study is expected to enrich studies related to the use of digital media such as WhatsApp and serve as a basis for designing strategies to increase student participation in the academic evaluation questionnaire process in higher education.